2012
DOI: 10.1007/s13524-011-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Employment Patterns of Less-Skilled Workers: Links to Children’s Behavior and Academic Progress

Abstract: Using data from five waves of the Women’s Employment Survey (WES; 1997–2003), we examine the links between low-income mothers’ employment patterns and the emotional behavior and academic progress of their children. We find robust and substantively important linkages between several different dimensions of mothers’ employment experiences and child outcomes. The pattern of results is similar across empirical approaches—including ordinary least squares and child fixed-effect models, with and without an extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 44 publications
0
86
1
Order By: Relevance
“…Recently, Berger (2012) showed that, in Germany, full-time working mothers are more satisfied with their lives than mothers who are not working due to family reasons and mothers in small part-time jobs (less than 20 h per week). However, Johnson et al (2012) found that maternal work has differentiated effects on children's cognitive and non-cognitive skills, depending on the extent of job stability and the job's cognitive skills requirements. These studies illustrate the need for further research on the driving mechanisms behind the positive relation between maternal employment and the cognitive development of young school-aged children.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Recently, Berger (2012) showed that, in Germany, full-time working mothers are more satisfied with their lives than mothers who are not working due to family reasons and mothers in small part-time jobs (less than 20 h per week). However, Johnson et al (2012) found that maternal work has differentiated effects on children's cognitive and non-cognitive skills, depending on the extent of job stability and the job's cognitive skills requirements. These studies illustrate the need for further research on the driving mechanisms behind the positive relation between maternal employment and the cognitive development of young school-aged children.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…There is, in fact, a surprisingly small body of evidence directly linking parental unemployment to indicators of the psychological well-being of children, with findings mostly suggesting relationships are either weak, often disappearing once other life events are controlled for or statistically insignificant (e.g., McMunn et al 2001;Sund et al 2003;Östberg et al 2006;Piko and Fitzpatrick 2007;Fröjd et al 2009). Also, with the notable exceptions of Johnson et al (2012) and Schaller and Zerpa (2015), this evidence is based on crosssectional data and consequently tells us very little about causality.…”
Section: Previous Researchmentioning
confidence: 97%
“…A literature is also emerging which suggests deleterious effects of parental displacement on children, including lower self-esteem and higher likelihood of grade repetition, dropout, and suspension or expulsion from school (Johnson, Kalil, and Dunifon 2012; Kalil and Ziol-Guest 2005, 2008; Stevens and Schaller 2010), educational attainment (Kalil and Wightman 2011), and lower income of children in adulthood (Page, Stevens, and Lindo 2009). These studies largely emphasize the deleterious effects of fathers’ loss of financial standing in the family among married couple households.…”
Section: Non-economic Effects Of Job Lossmentioning
confidence: 99%